(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
To investigate the effects of copper sulfate (CuSO4.5H2O) and zinc sulfate (ZnSO4) on growth performance, feed intake, feed efficiency and carcass characteristics of commercial broiler an experiment was conducted. Total 80 Cobb-500 of 07 days old chicks were randomly divided into four dietary groups having four replications in each. Four diets were considered: control (T0); CuSO4.5H2O @ 150 mg/kg of commercial diet (T1); ZnSO4 @100 mg/kg on diet (T2); and combination of CuSO4.5H2O + ZnSO4 @ 150 mg/kg + 100 mg/kg of diet (T3), respectively. Initial live weight, live weight gain and feed intake were recorded. Carcass characteristics were observed after slaughtering of birds. The final live weight was significantly (P<0.05) differed among the experimental groups where highest live weight was recorded in T2 (2440 g/bird) group. Broilers in T2 group showed the best feed efficiency (1.67) that varied significantly (P<0.05). Daily live weight gain was differed significantly (P<0.05) among the experimental groups where highest value at 3rd and 4th weeks of experiment was found in birds of T2 group. There were no significant (P>0.05) differences observed among the dietary treatment groups in terms of de-feathering percentages, liver, heart and abdominal fat weight. On the contrary, significant (P<0.05) difference were observed in carcass weight, where highest value was recorded in T3 group. Thigh and breast weight was also differed significantly (P<0.05) in T3 group compared to control and other groups. Use of copper sulfate pentahydrate in diet was economic in terms of cost benefit analysis. Res. Agric., Livest. Fish.7(3): 465-474, December 2020